A novel role for catalase B in the maintenance of fungal cell-wall integrity during host invasion in the rice blast fungus Magnaporthe grisea. - Skamnioti, P; Henderson, C; Zhang, Z; Robinson, Z; Gurr, S (2007)
Asexual spores of the rice blast fungus germinate to produce a specialized and melanized infection structure, the appressorium, which is pivotal to successful plant penetration. To investigate whether Magnaporthe grisea counteracts the toxic burst of H2O2 localized beneath the site of attempted invasion, we examined the temporal expression of five candidate antioxidant genes. Of these, the putatively secreted large subunit catalase CATB gene was 600-fold up-regulated in vivo, coincident with penetration, and moderately up-regulated in vitro, in response to exogenous H2O2. Targeted gene replacement of CATB led to compromised pathogen fitness; the catB mutant displayed paler pigmentation and accelerated hyphal growth but lower biomass, poorer sporulation, fragile conidia and appressoria, and impaired melanization. The catB mutant was severely less pathogenic than Guy 11 on barley and rice, and its infectivity was further reduced on exposure to H2O2. The wild-type phenotype was restored by the reintroduction of CATB into the catB mutant We found no evidence to support a role for CATB in detoxification of the host-derived H2O2 at the site of penetration. Instead, we demonstrated that CATB plays a part in strengthening the fungal wall, a role of particular importance during forceful entry into the host.